PERAN FAKTOR EMOSIONAL DAN KOGNITIF DALAM MEMBENTUK DINAMIKA KEPRIBADIAN RELIGIUS - Hanif, Muh.; Barokah, Nur Isnaeni (Jurnal Studia Insania, 2025)
This article examines how emotional and cognitive factors influence each other on a person's religious personality. Religious personality is a person's trait that shows beliefs, values and behaviors that are in accordance with the norms in the environment and the religious principles they adhere to. The purpose of this study is to gain an understanding of how emotional and cognitive aspects can influence a person's religious attitudes and actions. And how it impacts on a person's psychological balance and dynamics. The literature study method used in this study is a qualitative approach. This method involves looking at various theories of religion and psychology on how cognitive factors such as understanding, beliefs, and moral judgment are influential. In addition, emotional factors such as feelings of fear, affection, and tranquility, among others. This research shows that emotional factors play an important role in the formation of an individual's religious personality. When individuals experience an event in their lives that involves deep emotions in a religious or spiritual context, such as feelings of peace when performing worship or calmness in facing life's problems. This experience can be used as an individual's foundation in strengthening religious beliefs. The existence of negative emotions such as feelings of guilt or fear of sins that have been committed in their lives can also motivate individuals to get closer to religious teachings and the Creator. So that this can support the formation of a more balanced religious personality. Cognitive factors from the results of the study also show that a deep understanding of religious teachings has an impact on the formation of a consistent religious mindset. The process of deepening religious teachings and religious values through learning, discussion, and intellectual dialog is able to help individuals develop a strong religious personality. Cognitive abilities are also used to evaluate and interpret religious experiences to deepen religious beliefs in everyday life. The cooperation between these two factors can create good religious personality dynamics, where beliefs, emotions, and behaviors support each other in forming a good religious personality. Keywords: Emotional factors, cognitive factors, and religious personality Translated with DeepL.com (free version)